Patients at the centre after a health care incident: A scoping review of hospital strategies targeting communication and nonmaterial restoration. (20th December 2021) - Dijkstra, Rachel I.; Roodbeen, Ruud T. J.; Bouwman, Renée J. R.; Pemberton, Antony; Friele, Roland
Abstract: Objective: This study aimed to provide an overview of the strategies adopted by hospitals that target effective communication and nonmaterial restoration (i.e., without a financial or material focus) after health care incidents, and to formulate elements in hospital strategies that patients consider essential by analysing how patients have evaluated these strategies. Background: In the aftermath of a health care incident, hospitals are tasked with responding to the patients' material and nonmaterial needs, mainly restoration and communication. Currently, an overview of these strategies is lacking. In particular, a gap exists concerning how patients evaluate these strategies. Search Strategy and Inclusion Criteria: To identify studies in this scoping review, and following the methodological framework set out by Arksey and O'Malley, seven subject‐relevant electronic databases were used (PubMed, Medline, Embase, CINAHL, PsycARTICLES, PsycINFO and Psychology & Behavioral Sciences Collection). Reference lists of included studies were also checked for relevant studies. Studies were included if published in English, after 2000 and as peer‐reviewed articles. Main Results and Synthesis: The search yielded 13, 989 hits. The review has a final inclusion of 16 studies. The inclusion led to an analysis of five different hospital strategies: open disclosure processes, communication‐and‐resolution programmes, complaints procedures, patients‐as‐partners in learning from health care incidents and subsequent disclosure, and mediation. The analysis showed three main domains that patients considered essential: interpersonal communication, organisation around disclosure and support, and desired outcomes. Patient Contribution: This scoping review specifically takes the patient perspective in its methodological design and analysis. Studies were included if they contained an evaluation by patients, and the included studies were analysed on the essential elements for patients.